Prognostic value of TOP2A in bladder urothelial carcinoma and potential molecular mechanisms - Shuxiong Zeng; Anwei Liu; Lihe Dai; Xiaowen Yu; Zhensheng Zhang; Qiao Xiong; Jun Yang; Fei Liu; Jinshan Xu; Yongping Xue; Yinghao Sun; Chuanliang Xu (BMC Cancer, 2019)
Abstract Background The prognosis of bladder urothelial carcinoma (BLCA) varies greatly among patients, and conventional pathological predictors are generally inadequate and often inaccurate to predict the heterogeneous behavior of BLCA. This study aims to investigate the prognostic value and function of TOP2A in BLCA. Methods TOP2A expression level was examined by RNA-sequencing, quantitative real time polymerase chain reaction and immunohistochemistry from 10, 40 and 209 BLCA samples, respectively. Public databases were analyzed for validation. Cell proliferation, migration, invasion assays were performed to explore potential functions of TOP2A in BLCA. Flow cytometry was performed for cell cycle and apoptosis analysis. Univariable and multivariable Cox regression models were performed to identify independent risk factors for the prognosis of BLCA. Results We found TOP2A was significantly upregulated in BLCA samples, especially for high-grade and advanced stage tumors, compared with matched normal epithelial tissue. Univariable COX regression analysis revealed high TOP2A expression was significantly associated with poorer cancer-specific, progression-free and recurrence-free survival, but not independently of clinical characteristics in the multivariable models. Knockdown of TOP2A remarkably inhibited the proliferation of BLCA cells and non-cancerous urothelial cells. Furthermore, migration and invasion capacity of BLCA cells were strongly suppressed after TOP2A knockdown. Moreover, flow cytometry suggested TOP2A had anti-apoptotic function, and knockdown of TOP2A could induce resistance to doxorubicin in J82 cells. Conclusions In our study, TOP2A was overexpressed in BLCA and could serve as a prognostic biomarker for BLCA. Moreover, TOP2A is functionally important for the proliferation, invasion and survival of BLCA cells.